The trouble with Adineta vaga (Davis, 1873): a common rotifer that cannot be identified (Rotifera: Bdelloidea: Adinetidae) - Örstan, Aydin (Zootaxa, 2020)
My purpose here is to highlight three long-standing problems in the taxonomy of Adineta vaga (Davis, 1873) and its subspecies: 1. The lack of unique morphological criteria to identify the morphological variant (morphovariant) Davis described; 2. The lack of an evolutionarily meaningful subspecies definition applicable to parthenogenetic bdelloid rotifers; 3. The lack of compliance with the applicable articles of the International Code of Zoological Nomenclature (ICZN; https://tinyurl.com/y8f242an) when subspecies are assigned to A. vaga.